EFEKTIVITAS MODEL PJBL DENGAN AR UNTUK MENINGKATKAN KREATIVITAS SISWA PADA MATERI PERISTIWA ALAM DI KELAS 5 - Alma Linta Sakinah; Ani Nur Aeni; Regina Lichteria Panjaitan (Universitas Muhammadiyah Magelang, 2026)
This research was conducted to improve students' creativity in natural science learning on natural phenomena in fifth grade elementary school. The teacher-centered learning process causes students to be less active in developing ideas and producing work. This study aims to determine the effectiveness of the Project Based Learning (PjBL) model assisted by Augmented Reality (AR) on improving students' creativity. The study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research sample consisted of 2 schools, namely MIS Al-Islam Majalaya as the experimental class and MIS Al-Islam YUPPI as the control class. Data collection techniques used observation and tests (pretest and posttest). Data were analyzed using normality tests, homogeneity as prerequisite tests, hypothesis testing using t-tests and N-Gain. The results showed that there was an increase in student creativity in the experimental class using the AR-assisted PjBL model compared to the control class using conventional learning. The t-test results showed a sig value <0.05 so that the hypothesis can be accepted and there is a significant effect of the use of the AR-assisted PjBL model on students' creativity. The N-Gain value of the experimental class was in the high category, while the control class was in the low category. Thus, the AR-assisted PjBL model was effective in enhancing student creativity in natural phenomena material in fifth grade elementary school.